Estimation and Control of an UAV using Kalman Filter and Relay Feedback Autotuning Method - Ismail, Laith S.; Lupu, Ciprian (Opción, 2019)
An unmanned aerial vehicle (UAV) also known as Unmanned Aerial Systems (UAS) or Drone. UAV can be a remote-controlled aircraft or pre-programmed route. UAV are gaining popularity and demand in the commercial sector and for personal, hobbyist use. There is an increasing demand for UAV in areas such as thermal scanning, delivery, and mapping in areas, which are time-con- suming, difficult, or dangerous for a conventional approach. The design dis- cussed in this paper is basing on the development of UAV quadrotor helicopter (Quad Copter), software, modeling, estimation, and control system. The esti- mation depends on Kalman filter and the control part depend on Relay feed- back autotuning PID control method. The implementation is divided into two parts, simulation by using (Matlab) and real-time Implementation by using (LabVIEW and Arduino). The solution in this paper is used low-cost devices and tools such as Arduino and its use in building an educational platform and linking it with an industrial program such as the LabVIEW.